Da avenida central ao rio cidade, o Rio de Janeiro constrói e reconstrói a sua imagem - Tängari, Vera Regina (Paisagem e Ambiente, 1996)
The paper intends to describe the association between the patterns of open public spaces projects and urban landscape design in Rio de Janeiro, in both historical and contemporary approaches